KAMPANYE PUBLIC RELATIONS ANTI HOAKS BERBASIS KOLABORASI INFLUINCER DAN LEMBAGA PEMERINTAH: ANALISIS PESAN DAN RESPONS PUBLIK DI ERA PASCA-PANDEMI - Intan Cahyani Azelia Putri; Mayanda Gisti; Fitri Aisyah Nabila; Sri Hertimi (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2026)
The information crisis or infodemic in the post-pandemic era has mutated into a multi-sectoral threat, demanding a tactical reconstruction of the government's public communication model. Rigid bureaucratic communication approaches are deemed ineffective in countering decentralized disinformation. This study aims to analyze in depth the social media-based anti-hoax Public Relations (PR) campaign strategy utilizing a hybrid collaboration between government agencies and digital influencers, specifically focusing on message anatomy and public response mapping in the post-pandemic era. The research method applied a qualitative approach, combining Qualitative Content Analysis to dissect the message structure and Thematic Analysis to decode netizen comments. The findings reveal that persuasive-emotional and humorous narrative approaches (60%), which leverage the influencer's authenticity, are far more effective in penetrating the audience's information fatigue compared to rational-formal educational approaches (40%). Although this collaboration successfully garnered a majority of positive sentiments (55%) due to its ability to domesticate bureaucratic messages, the campaign still faced significant digital resistance (30% negative sentiments) driven by residual post-pandemic trust crises and organic public confirmation bias toward state institutions. This study contributes theoretically to the creditability transfer model in hybrid cyber communication and practically guides government PR practitioners in formulating dialogic anti-disinformation messages.